The black and white of the folklore / Izdihar Zakaria - Zakaria, Izdihar (Faculty of Information Management, 2015)
The article is about the black and white of the folklore. There are eight types of folklore in Malaysia. A few opus that are famous in Malaysia are Hang Tuah, Hikayat 1001 Malam, Pak Kaduk and many more. Folklore has its own black and white, means negative and positive. Nowadays, young generation did not have interest to know about the folklore. Throughout this article, there are reasons why people are no longer interested with folklore. There are not much research that have been done in Malaysia but the efforts that have been done by the researchers just to make sure the folklore is not been forgotten. This article also includes stories about two folklore stories.